2011
DOI: 10.1121/1.3654731
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic correlates of stress in Spanish infant-directed speech

Abstract: In infant speech research, children's input in often examined to determine at what age their production is affected by their language experience. In this study, we examined production of stress in Spanish infant-directed speech. Although the correlates of stress in English infant-directed speech have been examined, the same has not been done for Spanish. We analyzed infant-directed speech from eight native Spanish-speaking adults from Central and South America. The infant-directed speech was acquired by record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Specifically, the first question is whether the registers differ once any enhancement in lexical stressed syllables has been accounted for. This is relevant because Albin and Echols (1996) indicated that stressed and final unstressed syllables differed to a greater extent in IDS than ADS, regardless of their position in the utterance (see also Jacobson, Ward & Sundara, 2011, for evidence on the acoustic cues to stress in Spanish IDS). Thus, even once the confound with higher incidence of boundaries has been addressed, it remains possible that much of the differences between the registers could be due to the enhancement of stress specifically.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the first question is whether the registers differ once any enhancement in lexical stressed syllables has been accounted for. This is relevant because Albin and Echols (1996) indicated that stressed and final unstressed syllables differed to a greater extent in IDS than ADS, regardless of their position in the utterance (see also Jacobson, Ward & Sundara, 2011, for evidence on the acoustic cues to stress in Spanish IDS). Thus, even once the confound with higher incidence of boundaries has been addressed, it remains possible that much of the differences between the registers could be due to the enhancement of stress specifically.…”
Section: Introductionmentioning
confidence: 99%